Peningkatan Loyalitas Mahasiswa Yang Dipengaruhi Oleh Kualitas Pelayanan Akademik dan Kepuasan Mahasiswa (Studi Kasus Pada Mahasiswa S1 Dan D3 STIESIA Surabaya) - Novianto Eko Nugroho (Institut Teknologi Sepuluh Nopember, 2020)
Higher Education is the highest level of education in the education service business in Indonesia which produces bachelor or diploma graduates to meet the competitive needs of the workforce. This study aims to analyze the increase in student loyalty which is influenced by the quality of academic services and satisfaction of S1 and D3 STIESIA Surabaya students. This study uses a quantitative approach to determine the correlation of student loyalty which is influenced by the role of academic service quality and student satisfaction. This research method uses path analysis. The results showed an increase in student loyalty which was influenced by the role of academic service quality due to high student satisfaction